PENGARUH LEADER MEMBER EXCHANGE (LMX) DAN KEPUASAN KERJA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) GURU SD SWASTA DI KECAMATAN MENTENG JAKARTA PUSAT - Budijanto Budijanto (Universitas Negeri Jakarta, 2016)
The objective of this research was to understand the effect of leader member exchange (LMX) and job satisfaction on organizational citizenship behavior (OCB). It was a quantitative research. The research used is a survey method with a correlation approach. In this study serve as a sample of 81 teachers were selected based on random techniques (simple random sampling). Data were obtained by spreading questioner. This study was conducted in private elementary schools at the district Menteng, Central Jakarta. The result of this study are: (1) there is a positive direct influence of leader member exchange on OCB, (2) there is a positive direct influence of job satisfaction on OCB, (3) there is a positive direct influence between leader member exchange with job satisfaction. The implication of this research is an attempt to improve teachers’ OCB can be done by improving leader member exchange and job satisfaction.